2001
DOI: 10.2337/diacare.24.11.1882
|View full text |Cite
|
Sign up to set email alerts
|

Acute Fructose Administration Improves Oral Glucose Tolerance in Adults With Type 2 Diabetes

Abstract: OBJECTIVE -In normal adults, a small (catalytic) dose of fructose administered with glucose decreases the glycemic response to a glucose load, especially in those with the poorest glucose tolerance. We hypothesized that an acute catalytic dose of fructose would also improve glucose tolerance in individuals with type 2 diabetes.RESEARCH DESIGN AND METHODS -Five adults with type 2 diabetes underwent an oral glucose tolerance test (OGTT) on two separate occasions, at least 1 week apart. Each OGTT consisted of 75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
4
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 32 publications
4
69
4
4
Order By: Relevance
“…These results are similar to our recent study (Heacock et al, 2002) in which we found that 10 g of supplemental fructose, when given with an MGTT (50 g carbohydrate from instant mashed potatoes), had no effect on the postprandial glycemic response. The lack of efficacy when fed with a meal in the present study, as compared with a free glucose beverage (Moore et al, 2000(Moore et al, , 2001, may be related to the effects of free glucose on the absorption of fructose (Hoekstra & van den Aker, 1996;Shi et al, 1997). Rats have a higher capacity for absorbing free fructose compared with the human.…”
Section: Discussionmentioning
confidence: 62%
“…These results are similar to our recent study (Heacock et al, 2002) in which we found that 10 g of supplemental fructose, when given with an MGTT (50 g carbohydrate from instant mashed potatoes), had no effect on the postprandial glycemic response. The lack of efficacy when fed with a meal in the present study, as compared with a free glucose beverage (Moore et al, 2000(Moore et al, , 2001, may be related to the effects of free glucose on the absorption of fructose (Hoekstra & van den Aker, 1996;Shi et al, 1997). Rats have a higher capacity for absorbing free fructose compared with the human.…”
Section: Discussionmentioning
confidence: 62%
“…Type 2 diabetes is associated with impaired glucose tolerance and incomplete suppression of hepatic glucose production by hyperglycemia. These defects can be corrected, in part, by fructose administration (23,24), supporting a role for GK as a potential therapeutic target for type 2 diabetes. As a first step toward a novel therapeutic strategy for the control of glycemia in type 2 diabetes, our aim was to identify potent activators of GK that increase the affinity of liver cells for glucose and thereby lower the hepatic glucose threshold.…”
Section: Discussionmentioning
confidence: 95%
“…This mechanism enables rapid translocation of the enzyme to the cytoplasm in response to a rise in the extracellular concentration of glucose or fructose that occurs after a meal, resulting in a rapid increase in the rate of glucose phosphorylation (19). The role of this mechanism in regulating glucose metabolism is evident from the correlation between the rate of glucose phosphorylation and the free GK activity that is not bound to GKRP (19 -21) and from the stimulation of glucose disposal by fructose administration in vivo (22)(23)(24). Accordingly, it can be hypothesized that agents that cause either direct activation of GK or its dissociation from GKRP (25) are a potential strategy for stimulating hepatic glucose disposal in hyperglycemic conditions.…”
mentioning
confidence: 99%
“…Clinical translation of these findings has shown that small doses of fructose decrease the postprandial blood glucose response to oral glucose in people with5 and without type 2 diabetes 6. Under chronic feeding conditions, fructose, in exchange for other carbohydrates, has further been shown to decrease HbA1c in systematic reviews and meta‐analyses of controlled feeding trials 7, 8.…”
Section: Introductionmentioning
confidence: 99%